Efektivitas Metode Kunjung Karya Terhadap Kemampuan Menulis Teks Biografi Siswa Kelas X SMA Negeri 5 Pematangsiantar - Fathyah Ulfa Harahap (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study aims to describe the effectiveness of the visitation method on the ability to write biographical texts for class X students of SMA Negeri 5 Pematangsiantar. The population of this study were all students of class X SMA Negeri 5 Pematangsiantar with a total of 332 students. Determination of the sample was carried out using a purposive sampling technique. The samples obtained were 66 people, so that 33 people from the experimental class and 33 people from the control class were obtained. The method used in this research is the experimental method. The instruments used were tests and observations. The average score obtained by students from the experimental group using the visitation method was 84.39, while the average score obtained by students from the control group using the discussion method was 78.03. The results of data analysis on hypothesis testing show that tcount = 1.84. Then look at the ttable at a significant level α = 0.05 with df = n- k = 33-1 = 32, and the ttable value = 1.69 is obtained. So it can be concluded that tcount > ttable, namely 3.45 > 1.69. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that the visitation method is effective in improving students' ability to write biographical texts.